2020
DOI: 10.3390/jrfm13010014
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Distance and Entry Modes in Emerging Markets: Empirical Evidence in Vietnam

Abstract: Cultural distance is acknowledged as a crucial factor that significantly affects the entry mode selection of multinational enterprises. The purpose of this article is to analyze the relationship between cultural distance and entry mode choice by exploring a novel dataset of 5236 firms in Vietnam with foreign investment during the period 2005–2016. Although many studies were conducted about the cultural distance and entry mode nexus, most of the research mainly focuses on developed and developing countries, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(67 reference statements)
0
3
1
1
Order By: Relevance
“…This result was consistent with those of the studies by [32,60], who argued that a considerable cultural distance would result in an increase in prices and costs associated with contracting, negotiation, and monitoring and would create more risks, which in turn would encourage MNEs to choose JVE. However, this result contradicts the research conclusion of [61], who found a positive impact of cultural distance on WOE choice in Vietnam. Agriculture is a traditional field in Vietnam with long-standing customs and farming practices and where attention is often paid to experience and habits.…”
Section: Discussioncontrasting
confidence: 96%
“…This result was consistent with those of the studies by [32,60], who argued that a considerable cultural distance would result in an increase in prices and costs associated with contracting, negotiation, and monitoring and would create more risks, which in turn would encourage MNEs to choose JVE. However, this result contradicts the research conclusion of [61], who found a positive impact of cultural distance on WOE choice in Vietnam. Agriculture is a traditional field in Vietnam with long-standing customs and farming practices and where attention is often paid to experience and habits.…”
Section: Discussioncontrasting
confidence: 96%
“…High transactional costs encourage EMFs to safeguard their assets from the opportunistic behaviors of their partners (Brouthers and Brouthers, 2001). For example, when the cultural differences between Vietnam and their respective home countries are enormous, foreign investing firms prefer WOSs over JVs to operate independently and avoid the risk of uncertainty (Ha et al. , 2020).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Cultural distance, as measured by Hofstede's dimensions, influences market entry decisions, with higher cultural distance reducing the likelihood of international market entry (Rothaermel et al, 2006). It also affects the choice of entry modes in emerging markets and influences the success of market entry in small emerging markets (Ha et al, 2020;Gollnhofer & Turkina, 2015;Alexander et al, 2007). Additionally, cultural congruence can strengthen the internal marketing and employee satisfaction relationship, impacting market selection decisions (Huang & Rundle-Thiele, 2014).…”
Section: Cultural Distancementioning
confidence: 99%